2020
DOI: 10.1093/ofid/ofaa515.1910
|View full text |Cite
|
Sign up to set email alerts
|

LB-13. Economic and workload impact of COVID-19 pandemic on physicians in the United States: results of a national survey

Abstract: Background The United States (US) healthcare system has experienced enormous economic impact due to the COVID-19 pandemic, driven by both loss of revenue related to shutdowns and increased strain on resources. These factors have impacted the workload and finances of physicians. Methods A 31-item anonymous survey evaluating the psychological impact of the COVID-19 pandemic on physicians was developed at the University of Alaba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Recent public health crises, such as the coronavirus disease 2019 pandemic, have highlighted the importance of healthcare workers within the healthcare system. 1 2 Particularly, these events have demonstrated that good physical and mental health of medical personnel is essential for a well-functioning healthcare system. To address this, specific measures for managing the health of medical personnel are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Recent public health crises, such as the coronavirus disease 2019 pandemic, have highlighted the importance of healthcare workers within the healthcare system. 1 2 Particularly, these events have demonstrated that good physical and mental health of medical personnel is essential for a well-functioning healthcare system. To address this, specific measures for managing the health of medical personnel are needed.…”
Section: Introductionmentioning
confidence: 99%
“…A 2020 U.S. survey of 597 physicians found that 36.0% had assumed new nonclinical roles and responsibilities during the COVID-19 pandemic. 23 The combination of lean staffing, lack of resources and of work–life balance contributes to clinician burnout. VT can potentially improve clinician time management by reducing clinician workload and combating short consultation times that make it difficult to complete a detailed evaluation of risk factors.…”
Section: Resultsmentioning
confidence: 99%
“…Workload was demonstrated to have increased due to junior and middle-grade doctors’ treating more COVID-19 patients and adapting to changing COVID-19 protocols, mandatory use of PPE before seeing patients, longer working hours with no compensation for working beyond rostered hours, and rota changes to incorporate more on-call shifts [ 18 , 22 , 23 , 24 ]. Hoonakker et al found that on-call shifts, such as night shifts, have a higher workload than day shifts; regular shifts longer than 12 h are also associated with higher levels of burnout compared to those lasting 8 h [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%